Assessing the implementation of the child-friendly school system and its relationship to learner well-being in SOCCSKSARGEN - Bautista, Luzviminda; Libdan Jr., Ildefonso E. (Journal of Social, Humanity, and Education, 2025)
Purpose: This study examined the level of implementation of the Child-Friendly School System (CFSS) in the three city divisions of SOCCSKSARGEN and its relationship with learners' well-being. This study aimed to determine whether the CFSS contributes to positive emotional and educational experiences among learners. Research methodology: Using a descriptive-correlational design, the study gathered data from 237 respondents, including teachers, child protection coordinators, guidance counselors, and SSLG advisers from selected large, medium, and small schools in General Santos City, Koronadal City, and Tacurong City. The data collection instruments were based on DepEd Order No. 44, s. 2015, and a validated learner well-being scale. The statistical tools used included the mean and Pearson's r. Results: The findings revealed a high level of CFSS implementation across schools, with the highest teacher morale and academic success ratings. Learners’ well-being was also rated moderately across five domains: engagement, perseverance, optimism, connectedness, and happiness. A strong positive correlation (r = 0.6058, p < 0.05) was found between CFSS implementation and learner well-being. Conclusions: Stronger CFSS implementation is linked to better learner well-being, highlighting the importance of supportive and inclusive school environments. Limitations: The findings are limited to selected public secondary schools in SOCCSKSARGEN and rely on self-reported data, which may reflect subjective perceptions of the respondents. Broader generalizations beyond this region should be approached with caution. Contribution: This study provides empirical support for the CFSS as a critical approach to promoting student well-being and positive school outcomes. It also highlights the importance of sustained involvement of stakeholders.